A small heterocyclic molecule as a multistate transistor: a quantum many-body approach. Issue 33 (20th July 2021) - Ghosh, Dibyajyoti; Senapati, Parbati; Parida, Prakash; Pati, Swapan K.
Abstract : Using the quantum master equation for many-body Hamiltonian, this study computationally investigates highly non-linear current–voltage characteristics such as negative differential conductance, and Coulomb blockade in a small molecular bridge. Abstract : Weakly coupled molecular junctions are an active and important field of research due to their non-linear charge carrier transport. Herein, we investigate transport properties in a weakly coupled molecule, B2 C2 N2 H6, using a combined quantum many-body approach and kinetic (master) equations. Various non-linear current–voltage characteristics such as negative differential conductance (NDC), rectifications, and Coulomb staircase, which are the hallmarks of multistate transport devices, have been obtained. We further explore the effect of different perturbations such as gate voltage and perpendicular magnetic field on molecular transport. Depending on the strength of the applied perturbing field, several phenomena such as current switching, and suppression of NDC, have been realized in the device. This study demonstrates small molecules as promising components in next-generation nano-devices.